El gasto público y su incidencia en la desnutrición crónica en América Latina, periodo 2001-2019. - Terán García, Luis Atic (2022)
The objective of this research is to determine the incidence of public social spending on chronic malnutrition in Latin America during the period 2001–2019. An econometric model is estimated by the ordinary least squares method that relates the rate of chronic malnutrition, central government social public expenditure, extreme poverty, and GDP per capita as independent variables. Each of the variables is analyzed through the interpretation of graphs and statistical tables. An error correction vector model was estimated to establish the relationship between the variables. It was concluded that there is an inverse relationship, in the short and long term, between higher public social spending and a lower rate of chronic malnutrition in Latin American countries. In addition, there is a bidirectional causality in the Granger sense between the study variables. There is evidence of a positive impact on the reduction of chronic malnutrition with an increase in public social spending. The structure of the research project comprises five chapters. The first chapter presents the introduction, the research problem, the general objective, and the specific objectives. The second chapter includes the background and theoretical basis for each variable. The third section contains the research methodology. The fourth chapter contains the analysis of the results and the discussion. Finally, the fifth chapter contains the conclusions and recommendations for future research work.